Penerapan Metode Weighted Product Melalui Pendekatan Logika Fuzzy Pada Kasus Pemilihan Ketua Osim Man 7 Bireuen - vikki, Zakial (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
The use of computer technology has penetrated into various fields in completing work. Work that requires high accuracy, is carried out repeatedly and requires fast processing time is no longer appropriate for humans to do using conventional methods. Computer involvement has become an obligation in completing the work. One of the cases that require computer involvement is the case of decision making in an organization or company, or in computer science terms it is often called a decision support system. Many decision support models have been developed to improve the model's performance in performing calculations. In this study, a decision support model was also developed to choose the chairman of OSIM MAN 7 Bireuen using the Weighted Product (WP) method through a fuzzy logic approach as the initial weighting of criteria and alternatives. The results obtained are the calculation of the WP model more optimally with the help of weighting through a fuzzy logic approach. The final result of this research is the existence of a computerized system that is able to calculate alternative recommendations for the chairman of OSIM MAN 7 Bireuen, totaling 12 alternatives with 4 criteria